Effect of feeding a dried distillers’ grains with solubles diet on the metabolism of the intestinal wall in Guanling crossbred cattle: a preliminary assessment - Luo, Xiaofen; Zhang, Tiantian; Xu, Duhan; Zhu, Mingming; Zhang, Junjie; Zhang, Rong; He, Guangxia; Chen, Ze; Mei, Shihui; Zhou, Bijun; Wang, Kaigong; Chen, Chao; et al. (Frontiers in Veterinary Science, 2024)
Dried distillers’ grains with solubles (DDGS)-based diets are nutritious and can improve the inflammations and intestinal immunity in livestock. However, there is limited research examining the effect of feeding DDGS-based diets on changes in intestinal metabolites and related pathways in livestock. In this study, six Guanling crossbred cattle (Guizhou Guanling Yellow cattle × Simmental cattle) were selected and divided into a basal diet (BD) group and an experimental group fed with DDGS replacing 25% of the daily ration concentrates (DDGS) (n=3), respectively. Fresh jejunum (J), ileum (I) and cecum (C) tissues were collected for metabolomic analysis. Differential metabolites and metabolic pathways were explored by means of univariate and multivariate statistical analysis. In comparison to the J-BD group, 123 differential metabolites (VIP > 1, p < 0.05) were identified in the J-DDGS group, which (top 20) were mainly divided into superclasses, including lipids and lipid-like molecules, organic acids and derivatives, and organoheterocyclic compounds. Compared with the I-BD group, 47 differential metabolites were obtained in the I-DDGS group, which were mainly divided into superclasses, including lipids and lipid-like molecules and organic acids and derivatives. The C-DDGS vs. C-BD comparison revealed 88 differential metabolites, which were mainly divided into superclasses, including lipids and lipid-like molecules, organic oxygen compounds, and nucleosides. A total of 34 significant metabolic pathways were found (p < 0.05, −log(p) > 1.3). Among them, 3 significant pathways were significantly enriched in the J-DDGS group, 11 significant pathways were significantly enriched in the I-DDGS group, and 20 significant pathways were significantly enriched in the C-DDGS group. Importantly, primary bile acid biosynthesis, linoleic acid metabolism, and arachidonic acid metabolism correlated with intestinal inflammation and immunity by regulating gut microbiota, prostaglandin synthesis, and cell signaling. The data suggest that DDGS-fed cattle unregulated three metabolic pathways mentioned above and that a DDGS-based diet was able to maintain a balance of these three metabolic pathways, thus resulting in improvement of intestinal inflammation and enhanced immunity in cattle. In conclusion, the DDGS diet has the potential to improve intestinal inflammation and enhance the immunity of Guanling crossbred cattle by regulating the metabolic patterns of lipids and lipid-like molecules, organic acids and derivatives, and related metabolic pathways. These results allude to potential metabolic regulatory mechanisms of DDGS diets and also provide a theoretical basis for the application of DDGS in livestock feed.